AI-driven innovation within the ICT sector - Erika GRABOCKA; Ervisa NDOKA (Smart Cities and Regional Development Journal)
Innovation is pivotal in the competitive landscape of the Information and Communication Technology (ICT) sector, particularly in the context of rapidly evolving technological advancements. This research examines the instrumental role of Artificial Intelligence (AI) in facilitating innovation within the ICT sector, explaining its significance amidst accelerating technological progress. Utilizing articles from reputable high-impact journals published between 2019 and 2024, this paper meticulously analyzes recent contributions to clarify the integration of AI into innovation processes. The study builds upon foundational concepts in innovation management and contemporary advancements in AI frameworks, including AI Centered Design Thinking, the AI Adaptive Three-Horizons Framework, the AI Enabled Open Innovation Paradigm, the AI Specific Stage-Gate Model, and the AI Optimized Lean Startup Methodology, thereby contributing to the ongoing discourse surrounding AI integration in organizations. Employing a comprehensive literature review, the research systematically interrogates peer-reviewed articles from relevant databases, focusing on empirical evidence and theoretical insights regarding the influence of AI on innovation. The findings reveal that the strategic application of these frameworks significantly enhances decision-making efficiency, promotes user-centered design, and mitigates risks associated with AI deployment. The implications of this research are multifaceted, offering critical insights for academics, practitioners, and policymakers within the ICT sector. By highlighting the necessity of ethical considerations such as bias reduction and transparency in AI initiatives, the study emphasizes the imperative of responsible innovation practices. Ultimately, this research uniquely contributes to the field by providing a comprehensive synthesis of existing frameworks and their applicability to AI driven innovation, advocating for the continuous evolution of these frameworks to align with emerging technological trends. This focus affirms the relevance and significance of the study in advancing both theoretical understanding and practical application within the ICT sector.